Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/ju.0000000000001601
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Time to Definitive Treatment for Intermediate Risk and High Risk Prostate Cancer: Are Delays Associated with Worse Outcomes?

Abstract: Purpose: Prostate cancer is most commonly an indolent disease, especially when detected at a localized stage. Unlike other tumors that may benefit from timely receipt of definitive therapy, it is generally accepted that treatment delays for localized prostate cancer are acceptable, especially for low risk prostate cancer. Since treatment delay for intermediate risk and high risk disease is more controversial, we sought to determine if delays for these disease states negatively impacted oncological outcomes. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Prostate cancer is a relatively slow-growing malignancy and watchful waiting is a standard strategy in low-risk prostate cancer to decrease risk of overtreatment. In addition, evidence suggests that treatment delays up to 3 months can be considered safe for all localized prostate cancer patients [ 42 , 43 ]. Thus, one hypothesis that could be tested in future research is that the long treatment intervals for prostate cancer are due to many patients undergoing “watchful waiting,” although concerns about treatment morbidity or stigma could also play a role in some contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is a relatively slow-growing malignancy and watchful waiting is a standard strategy in low-risk prostate cancer to decrease risk of overtreatment. In addition, evidence suggests that treatment delays up to 3 months can be considered safe for all localized prostate cancer patients [ 42 , 43 ]. Thus, one hypothesis that could be tested in future research is that the long treatment intervals for prostate cancer are due to many patients undergoing “watchful waiting,” although concerns about treatment morbidity or stigma could also play a role in some contexts.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Van den Bergh et al found that curative treatment delay from months to even years were not associated with worse outcomes in men with LR prostatic cancer [ 29 ]. A more recent review found weak evidence of a higher risk of biochemical recurrence and worse pathological outcomes when surgery is delayed between 6 and 9 months, whereas worse survival outcome findings were not conclusive as an effect of delays beyond 12 months both for patients with intermediate risk and high risk PCa [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the evidence that earlier intervention is beneficial for our cohort of treatment-eligible patients with breast, colon, and lung cancer, [38][39][40] but potentially not for the patients with localized prostate cancer, 41 we further examined TTI by tumor site using a triple interaction between Medicaid expansion status, time period, and tumor site. Considering that Medicaid expansion under the ACA was targeted at low-income adults, an additional sensitivity analysis was conducted restricted to patients with the lowest countylevel median household (, $38,000 in US dollars) in the patient-level analysis and excluding median household income as a covariate.…”
Section: Sensitivity Analysismentioning
confidence: 99%